RANCANG BANGUN SISTEM MONITORING KONSUMSI ENERGI LISTRIK PADA PLTS BERBASIS IOT - Renta Risnauli N; Toibah Umi Kalsum; Yessi Mardiana (SKANIKA: Sistem Komputer dan Teknik Informatika, 2026)
Technological developments and the intensity of community activities have driven an increase in demand for electrical energy, thereby necessitating the exploration of sustainable alternative energy sources. One relevant solution is the utilization of Solar Power Plants (SPPs). This research focuses on the design and development of an energy consumption monitoring system for PLTS by adopting the Internet of Things (IoT) concept. The system development integrates PZEM-004T sensors to measure AC voltage, current, power, and energy parameters, ACS712 sensors for accurate current measurement, and special voltage sensors to monitor DC battery conditions. The entire control and data acquisition process is managed by the NodeMCU ESP32 module as the main processing unit. The data obtained is then displayed in real-time through the Blynk application interface. The research method applied is experimental, covering the stages of hardware design, software development, and overall IoT system integration. The evaluation results show that the system operates well, is capable of providing accurate electrical parameter readings, displays data with very low latency (around 0.1 seconds), and effectively supports remote ON/OFF control of electrical loads. Thus, this system is expected to contribute to improving